2014
DOI: 10.1073/pnas.1323955111
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 deficiency prolongs ovarian lifespan in mice

Abstract: Oocyte endowment dwindles away during prepubertal and adult life until menopause occurs, and apoptosis has been identified as a central mechanism responsible for oocyte elimination. A few recent reports suggest that uncontrolled inflammation may adversely affect ovarian reserve. We tested the possible role of the proinflammatory cytokine IL-1 in the age-related exhaustion of ovarian reserve using IL-1α and IL-1β-KO mice. IL-1α-KO mice showed a substantially higher pregnancy rate and litter size compared with W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 65 publications
5
70
0
Order By: Relevance
“…Our previous studies indicated that, throughout their reproductive lifespan, Il1a ‐knockout (KO) mice exhibit a significantly increased ovarian response to gonadotropins compared to wild‐type (WT) mice (Uri‐Belapolsky et al, ). We validated the cellular expression of Fshr in primary GCs from Il1a ‐KO mice, and found significantly higher Fshr transcript and FSHR protein abundance in ovaries of KO compared to WT mice (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies indicated that, throughout their reproductive lifespan, Il1a ‐knockout (KO) mice exhibit a significantly increased ovarian response to gonadotropins compared to wild‐type (WT) mice (Uri‐Belapolsky et al, ). We validated the cellular expression of Fshr in primary GCs from Il1a ‐KO mice, and found significantly higher Fshr transcript and FSHR protein abundance in ovaries of KO compared to WT mice (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the cytokines, IL1 is known to influence many aspects of ovarian function, including ovulation (Brännström, ; Gérard et al, ; Simón, ); however, which local processes are affected is not clear. IL1A is enriched within the oocyte and GCs throughout follicular development (Uri‐Belapolsky et al, ). We demonstrated that, in contrast to IL1B modulation (Ono et al, ), ovarian Il1a mRNA levels are reduced following gonadotropin triggering of ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Further defining the inflammatory milieu of the aging ovary and determining whether multinucleated macrophage giant cells are a cause or consequence of chronic inflammation are warranted and currently under investigation. Ultimately modulating pro-inflammatory pathways may be an important therapeutic avenue for prolonging reproductive lifespan because, for example, in a mouse knockout model of the pro-inflammatory cytokine IL-1α, the ovarian lifespan, pregnancy rate, and litter size were all increased relative to age-matched controls (Uri-Belapolsky, et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…However, controversy remains regarding whether the increased follicular atresia with aging is eliciting a pro-inflammatory response in the ovaries or if the increased overall pro-inflammatory status with aging is accelerating the depletion of the ovarian follicular reserve. Recently, it was demonstrated that IL-1 knockout mice have delayed ovarian aging (Uri-Belapolsky et al, 2014), suggesting an active role for the inflammatory response in the process of follicle depletion. We also observed that IL-1 production was one of the down-regulated biological processes in old df/df compared to old N mice.…”
Section: Discussionmentioning
confidence: 99%